Internal migration and development in East Timor : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Development Studies, Massey University, 2003 - Guterres, Aurélio Sérgio Cristóvão (Massey University, 2003)
Migration has been a subject of interest for scholars and students of development studies for many years, yet the conceptual tools for linking the process of migration and development have proven to be limited. Recent studies in developing countries have begun a re-assessment. Eschewing some of the old macro-economic models, which lay emphasis on rural to urban migration, scholars have employed broadly ethnographic methods to look at population movement and migration in terms of the meanings people ascribe to moving. They see cultural and social factors as being of prime importance. This study extends these approaches and provides an alternative way of looking at migration and development by employing ideas from Development Studies to differentiate population movement and migration resulting from "immanent development" from that which follows "intentional development" or state-led development. This thesis presents a model of that approach and focuses on internal migration and development in East Timor. East Timor has had a long history of colonial development with extremes of government policy under two different colonial regimes, the Portuguese and the Indonesian. Under Portuguese colonisation little development occurred, as the Portuguese were more interested in trade. Forced labour practices, involving the local population in the agricultural plantation activities, were imposed by the Portuguese to provide agricultural export commodities for colonial benefit. The plantation policy was part of a colonial strategy to keep the general population in the countryside, away from the capital Dili. On the other hand, the Indonesian period shows in very stark form the underlying intent of much rural development policy: the desire to impose order through controlling the pace of migration and slowly incorporating rural economies into a widening market system .It also shows that, despite such heavy control, forms of immanent development once unleashed will exert a strong influence on individual and family decisions to move. This study provides a new way of understanding migration and development from a micro-level perspective using a migration life stories approach. Migration life stories enable us to understand the complexity of migration and the relationship with development. The most exciting novel element of migration life stories approach is the ability of migrants to recall their migration histories and experiences, and to show how migrants’ histories and experiences are connected to migration in a particular context of their life. Thus using migration life stories, this study was able to show how migration is linked to development in the context of East Timor.
Keywords: Internal migration; East Timor; Social conditions; Economic conditions; Fields of Research::370000 Studies in Human Society::370500 Demography::370502 Migration